Endoscopic retrograde appendicitis techniques for the treatment of patients with acute appendicitis - Ye, Li-Ping; Mao, Xin-Li; Yang, Hai; He, Bi-Li; Zhu, Lin-Hong; Zhang, Yu (Zeitschrift für Gastroenterologie, 2018)
Objective The purpose of this study was to demonstrate the feasibility of endoscopic retrograde appendicitis therapy (ERAT) in treating patients with acute appendicitis.Materials and methods Between January 2014 and December 2014, 22 patients with acute appendicitis underwent ERAT. Patient demographics, colonoscopy findings, endoscopic retrograde appendiceal radiography (ERAR) findings, and treatment outcomes of the ERAT and adverse events associated with ERAT were analyzed.Results In this study, 22 patients with acute appendicitis underwent ERAT. The median age of the patients was 39.5 years. Colonoscopy findings included mucosal hyperemia and swelling of the appendiceal orifice and/or its surrounding mucosa (86.4 %, 19/22) and pus at the appendiceal orifice (40.9 %, 9/22). ERAR findings included irregular contour (76.2 %, 16/21), appendiceal lumen dilation (28.6 %, 6/21), appendiceal lumen stenosis (42.9 %, 9/21), and filling defect of the appendiceal lumen (23.8 %, 5/21). Deep intubation was successfully performed in 21 of the 22 patients (95.5 %). Sixteen patients underwent endoscopic appendiceal stent placement after endoscopic appendiceal irrigation (EAI) due to lumen stenosis of the appendiceal, excessive pus, or appendiceal fecalith, and the remaining 6 patients only underwent EAI. Among the 22 patients who underwent ERAT, their abdominal pain was noticeably relieved following the procedure. The main adverse events associated with ERAT were spontaneous discharge of the stent, recurrent abdominal pain, and recurrent appendicitis. During the follow-up (median 33 months), 2 patients underwent laparoscopic appendectomy.Conclusions ERAT provide a new alternative therapeutic method for patients with acute appendicitis, particularly for certain patients who are unwilling to undergo an appendectomy.
Keywords: endoscopic techniques; endoscopic appendiceal irrigation; endoscopic diagnosis; endoscopic therapy; acute appendicitis